2019
DOI: 10.3390/w11112361
|View full text |Cite
|
Sign up to set email alerts
|

Estimating River Discharges in Ungauged Catchments Using the Slope–Area Method and Unmanned Aerial Vehicle

Abstract: River discharge is of great significance in the development of water resources and ecological protection. There are several large ungauged catchments around the word still lacking sufficient hydrological data. Obtaining accurate hydrological information from these areas is an important scientific issue. New data and methods must be used to address this issue. In this study, a new method that couples unmanned aerial vehicle (UAV) data with the classical slope–area method is developed to calculate river discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Our results are in agreement with Yang et al [28], who achieved a minimum prediction error (indicated in their work as relative accuracy) equal to 9.14%, computed by comparing the global flow resistances based on field measurements with those retrieved by employing a model based on unmanned aerial vehicles (UAV) techniques, in a river partially covered by emergent riparian vegetation. This is a promising finding since it demonstrates that the application of a simple methodology, like DCM [11] combined with one of the four examined composite cross section methods [12][13][14][15], can lead to results comparable with those obtained by using more complex models.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with Yang et al [28], who achieved a minimum prediction error (indicated in their work as relative accuracy) equal to 9.14%, computed by comparing the global flow resistances based on field measurements with those retrieved by employing a model based on unmanned aerial vehicles (UAV) techniques, in a river partially covered by emergent riparian vegetation. This is a promising finding since it demonstrates that the application of a simple methodology, like DCM [11] combined with one of the four examined composite cross section methods [12][13][14][15], can lead to results comparable with those obtained by using more complex models.…”
Section: Discussionsupporting
confidence: 92%
“…Yang et al [82] calculated the river discharge in ten sections in the Tibetan Plateau and Province of Xinjiang by (i) retrieving the parameters of the slope-area method using an UAS to generate a digital orthophoto map and a DSM and (ii) applying three different formulas (Manning-Strickler, Saint-Venant and Darcy-Weisbach). In Yang et al [83], UAS remote sensing, high altitude remote sensing and in situ measurements are combined to estimate river flow in medium/small wide shallow rivers in arid areas. The attenuation coefficient and discharge of the ungauged Hotan river (Central Asia) was calculated by applying energy equations and a trapezoidal cross-section discharge equation.…”
Section: Surface Velocity and Flow Estimationsmentioning
confidence: 99%
“…Riggs proposed the slope-area method (SAM), a classic hydraulic equation to calculate the runoff by using the slope and river cross-sectional area [38], that is based on physical laws and mathematical derivation and widely used for calculating the discharge of small-and medium-sized rivers [39,40]. We used three-dimensional surface data obtained from UAV-based remote sensing to calculate the river flow [41] with the SAM [42,43]. The equations used for the SAM calculation are as follows:…”
Section: Calculating River Flowmentioning
confidence: 99%
“…where v is the average flow, m/s; k is the conversion factor, m 1/3 /s (=1); n is the empirical roughness coefficient; the hydraulic radius R is the ratio of the river section area A to the wet cycle L; J is the hydraulic gradient of the river channel; and Q is the river flow, m 3 /s. The R and J values were obtained from UAV-based remote sensing [42,43].…”
Section: Calculating River Flowmentioning
confidence: 99%